Is the currency risk priced in equity markets? - Francesco Giurda; Elias Tzavalis (Queen Mary University of London, Department of Economics, 2004)
In this paper we investigate whether the currency risk is priced in international stock markets. We suggest a parsimonious version of the international capital asset pricing model with an EGARCH-M(1,1) specification of the second moments' dynamics of stock and currency returns, assuming that the latter follow a multivariate t-distribution. This specification allows for asymmetric responses of volatility to stock and currency news, including leverage effects. Our results suggest that the currency risk is priced in international stock markets, once asymmetries in volatility are taken into account. The currency premium is found to be significant on both statistic and economic grounds. We find that a dynamic portfolio strategy that hedges against currency changes provides higher returns (as a reward for currency premium) than a strategy which ignores them.
Keywords: C32; C52; C53; G11; G12; 330; International asset pricing; Currency risk; Multivariate EGARCH; Density forecast; Dynamic hedging strategies; Wechselkursrisiko; Capital Asset Pricing Model; ARCH-Modell; Hedging; Sch\~AƒÂtzung; Gro\~AƒÅbritannien; USA; Deutschland; Japan